From the concept of urban noise to the one of sonorous landscape (2006)
Noise pollution is one of the environmental problems that humanity confronts nowadays. Different studies have shown that noise affects people, producing physical and psychological effects. Moreover, international institutions have included noise as environmental topic of priority research. The aim of this work is to review and discuss the evolution of noise assessment on urban environments. Numerous studies have been carried out to know the negative effects of urban noise; annoyance has been found as one of the more important in terms of the number of affected people. Standards and recommendations have been published to protect people. However, recent investigations have shown the complexity of human response to noise and that noise level is not the only variable that affects it. Nowadays sound environment is studied from an integral point of view. This new approach is based on the concept of soundscape, in which sound is not considered just a mere physical element of the urban context but as a means of information and communication between a person and the urban environment.